2020
DOI: 10.1186/s12903-020-01317-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apexification on occlusal resistance of immature teeth

Abstract: Background Strain distribution was investigated to assess the occlusal resistance alterations in immature teeth under different occlusal force. Methods In vitro apexification models of teeth with a funnel-shaped immature apex were obturated with mineral trioxide aggregate (MTA; ProRoot MTA) using different combinations of core materials (10/group): group 1, full-length orthograde obturation of MTA; group 2, a 5-mm MTA apical plug with a composite core; group 3, a 5-mm MTA apical plug and back-filling with war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The previous studies demonstrated root resorption in animal models when bite force was applied, leading to periodontal tissue dysfunction owing to occlusal insufficiency [ 37 , 38 ]. During facial growth and development, mechanical stress on deciduous teeth increases gradually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies demonstrated root resorption in animal models when bite force was applied, leading to periodontal tissue dysfunction owing to occlusal insufficiency [ 37 , 38 ]. During facial growth and development, mechanical stress on deciduous teeth increases gradually.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies, such as genetic data analysis and basic physiological research, are warranted to clarify the details of root resorption in retained mandibular second deciduous teeth with the congenital absence of subsequent permanent teeth. With 228 partially edentulous patients accounting for up to 180 different patterns of missing teeth [ 38 ], the patterns of missing teeth among these patients differed extensively. In cases where several consecutive teeth are missing, or there are concomitant abnormalities in the crown morphology, such as dwarf teeth, it is often difficult to achieve space closure by tooth movement alone.…”
Section: Discussionmentioning
confidence: 99%
“…The success of root maturation after regenerative endodontic procedures in immature teeth with apical periodontitis and pulp necrosis is not always possible. In particular, immature roots with previously unsuccessful endodontic treatments fail to continue further root development in width and length [ 28 ]. Therefore, apexification could be considered as an alternative strategy to achieve apical barrier formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great importance to preserve the vitality of the pulp until root development is complete ( Table 1 ). Young permanent teeth with necrotic pulp and periapical processes are a significant treatment challenge due to the lack of an apical barrier and the impact on periodontal tissues [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%